Factors that influence the health status of immigrants living in Greece - Sourtzi Panayota; Galanis Petros; Konstantakopoulou Olympia; Siskou Olga; Kaitelidou Daphne (AIMS Press, 2020)
Aim: To examine the health status of immigrants living in Greece and investigate the factors that influence it. Methodology: A cross-sectional study with 1152 immigrants (response rate = 60%) was conducted during April 2013 to March 2014. Regarding the sampling method, as there is no accurate census of immigrants in Greece the snowball sampling was used. Data collection included demographic characteristics, health status, medication and self-reported preventive health examinations of immigrants (blood count, blood pressure, cholesterol, and blood sugar measurement). Results: The majority of immigrants originated from Albania (51.4%), while 52.6% were males with mean age 37.6 years. Of those 63.5% were working, 80.9% had legal documents for living and working in Greece and 58.2% had valid health and social security. Most of the immigrants (66.6%) considered their health as good/very good. Immigrants without health insurance, lower monthly family income and worst self-reported health did not adhere with their medication treatment due to cost. Immigrants with legal documents and health insurance performed more often blood count measurement, blood pressure measurement, cholesterol measurement and blood sugar measurement. Increased monthly family income was also associated with higher probability of blood count measurement. Very poor/poor/average self-reported health and increased age were associated with higher probability of taking medicines for chronic diseases. Conclusions: Self-reported health of immigrants in Greece is good/very good while absence of health insurance and legal documents, lower income and worst self-reported health are associated with worst health outcomes.